Project cost performance forecasting system - Mohd. Nasira, Siti Rashidah; Abd. Majid, Muhd. Zaimi (2006)
Forecasting project cost performance is a paramount important to the project controls process in construction industry. In making profits, today’s construction organization requires an ability to predict, well ahead of time, project performance. Thus, necessary and timely corrective actions need to be taken if project lagged of time or exceed budget. As a consequence, there have been many studies on this aspect which develop theories and methods to improve the forecasting system. Through a critical review of forecasting method approaches, a number of issues are highlighted that concern of the types of forecasting approach, forecasting project cost performance at completion, cost variances in project performance, other critical parameters of project performance to be incorporated along with cost and ineffective methods in generating reliable and timely results and therefore providing early warning of cost performance overruns. Also, it provides fundamental for forecasting system designed for adaptability in a challenging environment and focused throughout on the delivering successful project.